Planejamento e gestão do ambiente construído em universidades públicas - Esteves, Juliana Cardoso (Universidade Federal de São Carlos, 2013)
Universities go through constant physical expansion processes, which requires planning, design and investment in infrastructure. Public universities often maintain their own design offices and teams responsible for planning and management of physical space, as well as for the supervision of building processes and others, which have a relation to society. This research aims to study and characterize design process and physical space planning and management inside public universities, through the systematization of processes and of internal flows of activities and information and, also, by identifying the key problems within these processes, as well as the relations between such processes and institutional planning instruments such as Urban Master Plans and Institutional Development Plans. The work presents a literature review and case studies of three Brazilian public universities, focusing its planning and design offices. As its main results, we present a diagnosis of the maturity stage of planning and management of the built environment processes within those institutions, characterize best practices related to those processes and propose some guidelines for project development in public universities.
Keywords: Planejamento físico-ambiental; Gestão de projetos; Universidades e faculdades públicas; Edifícios públicos; Physical space management; Design process; University; Public building; ENGENHARIAS::ENGENHARIA CIVIL